Destination Branding dan Optimalisasi Performa Kelompok Sadar Wisata (Pokdarwis) melalui Sistem Informasi Desa Wisata Berbasis Bauran Pemasaran 9P - Yerik Afrianto Singgalen (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The challenge in destination branding is the support of all stakeholders in the tourism sector through collaboration and synergy in tourism potential management. To improve the positive image of the destination, digital campaigns are one of the practical approaches to attract tourist visits. Meanwhile, the Kelompok Sadar Wisata (Pokdarwis) is a driving force that triggers local communities' participation and encourages tourism development in each region. However, there are challenges in realizing the synergy of stakeholders' interests to improve the positive image of tourism villages. This research aims to design a tourism village information system that encourages the performance of Pokdarwis while destination branding. In addition, the framework used in system design is design thinking based on the 9P marketing mix (Product, Price, Promotion, Place, People, Physical Evidence, Process, Performance, and Partnership). The results of the system design show that Pokdarwis is essential as an actor who has access to data and information management and system operations integrated with the 9Ps with the following description: product is a series of activities or services in a tourist village that tourists can purchase; price, is the value of the service package that can be accessed by tourists based on the latest price; promotions, are added value and special prices offered based on time frames; place, is the location of activities offered by the theme of the activity; people, emphasizing the party in charge involved in each activity; physical evidence emphasizes the facilities available to support activities; process, is the flow of ordering and using the services offered; performance, emphasizing the history of previous service delivery; Partnership, is a partner involved directly or indirectly as a supporter of tourism services. This shows that the tourism village information system based on the 9P marketing mix can optimize the performance of Pokdarwis while forming destination branding.